Изменение показателей дыхания и кровообращения при нагрузках ступенчато-повышающейся мощности у юных пловцов - Баламутова, Н. М.; Блошенко, Елена Ивановна; Борейко, Наталья Юрьевна (Національний педагогічний університет ім. М. П. Драгоманова, 2019)
Многочисленными исследованиями доказано положительное влияние плавания на здоровье занимающихся. Поэтому вопрос о воздействии занятий плаванием на организм юных пловцов следует рассматривать с учетом индивидуальных анатомо-физиологических особенностей. Целью настоящего исследования явилось изучение влияния физических нагрузок ступенчато-повышающейся мощности на дыхание и кровообращение юношей 15-16 лет, регулярно посещающих секцию по плаванию. Результаты исследования показателей дыхания и кровообращения при заданной нагрузке позволяет охарактеризовать функциональные возможности юношей-пловцов. Было доказано, что система подготовки юных пловцов строилась с учетом возраста и анатомо-физиологических особенностей их организма, а физические нагрузки были адекватны их физиологическому развитию.

The positive is well – proven numerous researches influence swimming on the health of occupying. Therefore question about affecting of employments swimming organism of young swimmers it is necessary to examine taking into account individual of anatomical and physiological features. The aim of the real research was a study of influence of physical activities of step-rising power on breathing and circulation of blood of youths 15-16, regularly visitant a section on swimming. A result of research of indexes of breathing and circulation of blood at the set loading allows describing functional possibilities of youths - swimmers. It was well - proven that the system of preparation of young swimmers was built taking into account age anatomical and physiological features of their organism, and physical activities were adequate to their physiological development. Modern living conditions are characterized by rapid development of automation of production and information technologies, which deprives a person of motor activity. Swimming is one of the most effective means of motor activity that positively influences the functional state of the cardiovascular and respiratory system. Numerous studies have already shown the positive effect of swimming on the health of the practitioners. It should not be forgotten that despite the significant differences in the functional state of the apparatus of external respiration and blood circulation in young swimmers and their peers - not athletes, the organism in both of them has not yet reached maturity and their age development and formation occurs in accordance with a single general biological regularities. Therefore, the question of the impact of swimming lessons on the body of young swimmers should be considered not only in terms of the impact on it of the specific features of the aquatic environment and the requirements of modern training, but also taking into account anatomical and physiological features.
Change of indexes of breathing and circulation of blood at loading of step-rising power for young swimmers
Keywords: подростки; физическая нагрузка; дыхание; кровообращение; teenagers; physical activity; breathing; circulation of blood